Adsorption of copper(II) in biochar-humic acid–water system - Yingquan Li; Baowei Zhao; Tingting Shang (Scientific Reports)
Abstract Both biochar and humic acid adsorb heavy metals, but their combined effect has rarely been reported. In this paper, the adsorption of Cu(II) by single biochar (BS) and biochar with humic acid (BS + HA) in aqueous solution were studied, and the effects of solution pH, initial Cu(II) concentration, temperature and Ca2+ ionic strength on the adsorption of Cu(II) were investigated. The results showed that under the same time, the adsorption of Cu(II) under the BS and BS + HA systems showed an increasing trend with the increase of pH, and the maximum adsorption capacity of the BS + HA system was reached at a pH of about 4, while the BS system alone exhibited a noticeable lag. The increase of the initial concentration of Cu(II) also promoted the adsorption capacity of the two systems, and the adsorption of Cu(II) by the BS and the BS + HA systems was a spontaneous adsorption process, and the elevation of the temperature effectively promoted the adsorption of Cu(II). The addition of Ca2+ could promote the adsorption efficacy of the single BS system, but had little effect on the BS + HA system. Overall, the BS + HA system showed better adsorption than the single BS system, and the addition of humic acid enhanced the adsorption performance of biochar to Cu(II). The results could provide a theoretical basis for the combined action of biochar and humic acid on the remediation of Cu(II) contaminated water.